YUSUF HAMADANI - A GREAT REPRESENTATIVE OF THE TEACHING OF SUFIS, A SUFI SCIENTIST (Scientific journal of the Fergana State University, 2025)
This article highlights Yusuf Hamadoni's contribution to the doctrine of Sufism, the fundamental essence of the doctrine of Sufism, and the various definitions given in scientific and religious literature. It also highlights the content of the definitions given to the ideas of Sufism as a science, as a movement, and as a "teaching," and concludes that Sufism should be viewed as a religious and pedagogical doctrine.